Characterization of 2 Neisseria gonorrhoeae Strains With High-Level Azithromycin Resistance Isolated in 2015 and 2018 in Japan. Issue 7 (July 2021) - Shimuta, Ken; Lee, Kenichi; Yasuda, Mitsuru; Furubayashi, Keiichi; Uchida, Chiaki; Nakayama, Shu-ichi; Takahashi, Hideyuki; Ohnishi, Makoto
Abstract : Abstract: We identified and characterized the first 2 Neisseria gonorrhoeae strains with high-level azithromycin resistance isolated in Japan. These were in the clade of ceftriaxone- and azithromycin-resistant strains isolated in Australia and the United Kingdom. The multilocus sequence typing, N. gonorrhoeae multiantigen sequence typing, and N. gonorrhoeae sequence typing for antimicrobial resistance types of these strains were found in gonococci from eastern Asia. Abstract : We characterized 2 Neisseria gonorrhoeae strains with high-level azithromycin resistance. These are the first high-level azithromycin-resistant gonococcal strains confirmed in Japan.Supplemental digital content is available in the text.